2011
DOI: 10.1111/j.1600-0463.2011.02814.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of the expression of TGF‐β pathway inhibitors, Smad‐7 and Ski, on invasive breast carcinomas: relation to biologic behavior

Abstract: The aim of our study was to investigate the expression of Smad-7 and Ski proteins in invasive breast carcinomas, to determine their clinicopathological value and their influence on carcinomas biologic behavior. Immunohistochemistry was applied on 150 invasive breast carcinomas to detect the expression of Smad-7 and Ski. Their correlation to clinicopathologic parameters and markers of metastasis was statistically processed using chi-squared test. Overall and disease-free survival was assessed using Kaplan-Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Theohari and colleagues investigated the expression of Smad7 in 150 invasive breast carcinoma specimens and showed that Smad7 levels positively correlate with tumor size, stage, matrix metalloproteinase (MMP)-9 and MMP-14 expression thus resulting in an aggressive phenotype [56]. However, experimental evidence suggests that Smad7 can regulate either positively or negatively breast carcinogenesis.…”
Section: Expression and Role Of Smad7 In Cancermentioning
confidence: 99%
“…Theohari and colleagues investigated the expression of Smad7 in 150 invasive breast carcinoma specimens and showed that Smad7 levels positively correlate with tumor size, stage, matrix metalloproteinase (MMP)-9 and MMP-14 expression thus resulting in an aggressive phenotype [56]. However, experimental evidence suggests that Smad7 can regulate either positively or negatively breast carcinogenesis.…”
Section: Expression and Role Of Smad7 In Cancermentioning
confidence: 99%
“…Western blot was done to detect the protein level of SND1, Smurf1, and RhoA. F, the total cell lysates of different treated MCF-7 cells (top) were immunoprecipitated with anti IgG (lanes 1-4) or anti-RhoA (lanes [5][6][7][8] antibody, then subjected to antiRhoA (top) or antiubiquitination (bottom) immunoblotting.…”
Section: Snd1mentioning
confidence: 99%
“…The misregulation of TGFb signaling may promote tumor invasion and migration, leading to detrimental consequences for prognosis in patients with breast cancer (3)(4)(5). The TGFb signaling pathway contains different R-Smads (Smad1, Smad2, Smad3, and Smad5) and co-Smad (Smad4) transcription factors (6)(7)(8). Smad1, Smad5, and Smad8 are specifically activated by the bone morphogenetic protein (BMP) receptors, whereas Smad2 and Smad3 are specifically activated by TGFb-related receptors (9).…”
Section: Introductionmentioning
confidence: 99%
“…66 In invasive breast cancer tissue samples, increased cytoplasmic SKI expression is inversely associated with tumor size, stage and lymph node status and positively associated with longer disease-free survival. 67 Research on the consequences of SKI action on Smad3 linker phosphorylation is actively being pursued in breast cancer cells.…”
Section: Additional Mechanisms Of Smad3 Regulationmentioning
confidence: 99%